2018
DOI: 10.1042/bsr20181011
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of artemisinin extract against cholestasis induced via lithocholic acid exposure

Abstract: Obstructive cholestasis characterized by biliary pressure increase leading to leakage of bile back that causes liver injury. The present study aims to evaluate the effects of artemisinin in obstructive cholestasis in mice. The present study was carried out on 40 adult healthy mice that were divided into 4 groups, 10 mice each; the negative control group didn’t receive any medication. The normal group was fed normally with 100 mg/kg of artemisinin extract orally. The cholestatic group fed on 1% lithocholic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…For example, glycyrrhizin, the main component of licorice, can promote the detoxification process of LCA by accelerating CYP3A catalyzation ( Wang et al, 2012 ). Both juniperus procera extract and artemisinin treatment prevent hepatotoxicity and cholestasis caused by LCA exposure ( Alkhedaide, 2018 ; Alkhedaide et al, 2018 ). Lysimachia christinae Hance also improves LCA-induced cholecystitis ( Yang et al, 2011 ).…”
Section: Detoxification Of Lcamentioning
confidence: 99%
“…For example, glycyrrhizin, the main component of licorice, can promote the detoxification process of LCA by accelerating CYP3A catalyzation ( Wang et al, 2012 ). Both juniperus procera extract and artemisinin treatment prevent hepatotoxicity and cholestasis caused by LCA exposure ( Alkhedaide, 2018 ; Alkhedaide et al, 2018 ). Lysimachia christinae Hance also improves LCA-induced cholecystitis ( Yang et al, 2011 ).…”
Section: Detoxification Of Lcamentioning
confidence: 99%
“…Increased production of DCA is associated with the formation of hepatocellular carcinomas and intestinal cancers (Dong et al, 2018;Yoshimoto et al, 2013). LCA is implicated in intrahepatic cholestasis (Alkhedaide et al, 2018;Lucangioli et al, 2009). The toxicity of BAs is partially attributed to their detergent properties, which is dependent on their hydrophilicity.…”
Section: Effect Of Ciprofloxacin and Moxifloxacin On Ba Composition I...mentioning
confidence: 99%
“…This effect was mediated mainly by inhibiting the activation of NF-κB and MAPK pathways [ 109 ]. A later study suggested that oral exposure to lithocholic acid (LCA) caused liver injury, but the anti-inflammatory activity of artemisinin extract in liver tissues increased the expression of GSH in a LCA-induced mouse model [ 110 ]. Chen and colleagues reported that DHA treatment improved hepatic necrosis and infiltration of inflammatory cells, thus playing a protective role in bile duct ligation (BDL)-induced injury in a rat model.…”
Section: Pharmacological Effects Of Artemisinin and Its Derivatives In Vitromentioning
confidence: 99%